Quantum MDS Codes over Small Fields - Grassl, M.; Roetteler, Martin (Proceedings of the 2015 IEEE International Symposium on Information Theory (ISIT'15), Hong Kong, 2015)
We consider quantum MDS (QMDS) codes for quantum systems of dimension q with lengths up to q2 + 2 and minimum distances up to q + 1. We show how starting from QMDS codes of length q2 + 1 based on cyclic and constacyclic codes, new QMDS codes can be obtained by shortening. We provide numerical evidence for our conjecture that almost all admissible lengths, from a lower bound n0(q,d) on, are achievable by shortening. Some additional codes that ﬁll gaps in the list of achievable lengths are presented as well along with a construction of a family of QMDS codes of length q2 +2, where q = 2m, that appears to be new.
See also arXiv preprint arXiv:1502.05267